Konsentrasi dan kemurnian ekstraksi DNA metode sonikasi dan spin column dari sampel dahak penderita tuberkulosis - Saputra, Fitrianingsih; Indra, Asep Iin Nur; Djuminar, Ai; Merdekawati, Fusvita; Nurhayati, Betty (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2024)
Background: The Polymerase Chain Reaction (PCR) method can identify Mycobacterium tuberculosis in a sputum sample of a patient with TB (TB). One crucial step to ensure accurate PCR results is the DNA extraction process. Objective: The research aims to compare the concentration and purity of DNA from the sputum of TB patients using ultrasound and spin column extraction techniques. Methods: The research uses descriptive study designs with post-only design strategies. The primary data was derived from 18 sputum specimens from TB patients. Concentration measurement and DNA purity testing using a nanodrop spectroscopic photometer. Results: DNA extraction by ultrasound method has an average concentration of 18.9 ± 8.5 ng/L, with a peak of 37.6 ng/ L. The spin column method produces an average of 55.5 ± 27.9 ng/μL; the peak is 105.0 ng/ μL. The purity value of the DNA extract is in the range of 1.8 ± 2.0 with the ultrasound method of 61% and the spin column of 78%. Conclusion: The sonication method has a lower average concentration and a higher percentage of purity than the spin column method, and there are differences in concentrations and purity values between the two methods.